Notice of the Discovery of a Bronze-Age Cist and Urn in the West Links, North Berwick: With Notes on the Bones found in the Cist - Cree, James Edward; Richardson, James S; Crombie, J Frank (Proceedings of the Society of Antiquaries of Scotland, 1907)